Therapeutic Patient Education for Adrenal Insufficiency under COVID-19 Pandemic Conditions - Kienitz, Tina; Hahner, Stefanie; Burger-Stritt, Stephanie; Quinkler, Marcus (Experimental and Clinical Endocrinology & Diabetes, 2020)
Adrenal insufficiency (AI) requires life-long treatment with glucocorticoid replacement therapy. Over- or under-substitution carries the risk of increased morbidity in the form of side effects or adrenal crises. Glucocorticoid replacement therapy needs to be flexible with dose adaptation in special situations. This could not be managed by medical personnel on a daily basis, but requires an educated patient who has a good knowledge of the disease, understands his medical therapy and is able to perform situational dose adaptation. The rarity of the disease in combination with the need to respond to stressful situations with rapid glucocorticoid dose adjustment underlines that a well-trained patient is crucial for optimal management of the disease.In this literature review we provide background information further clarifying the need of education in patients with AI including the current shortcomings of medical therapy and of the treatment of patients with AI. We outline the aims of therapeutic patient education, present the concept of structured patient education in Germany, and discuss available results of patient group education programs. Furthermore, we propose strategies how therapeutic patient education for adrenal insufficiency can be organized under COVID-19 pandemic conditions.
Keywords: adrenal crisis; hydrocortisone; secondary adrenal insufficiency; emergency card